Interaction of leishmania (L.) chagasi with the lulo cell line in different environmental conditions (2006)
There are unknown or poorly understood events in the Leishmania-host cell interactions that merit studies in new in vitro models. The aim of the present work was to evaluate Leishmania chagasi interaction with a cell line (Lulo) previously established and derived from Lutzomyia longipalpis embryonic tissues, bearing different temperatures and CO 2 concentrations in mind and morphometric changes of the cells. The J774 cell line was used as positive control of the infection. The L. chagasi MH/CO/84/CL-044B strain was used for infection assays. The parasites were added to adherent cells, in Lulo as well as J774, in a 5:1 ratio. Incubation was at 28°C and 37°C, in the absence and presence of CO 2. A morphometric study of the cells was carried out before and after infection. Both parasite and cell ultrastructure characteristics were analyzed by electron microscope. The greatest percentage of infection in the Lulo cells at 28°C (26,8%) was registered on day six post infection, while at 37°C, in the absence of CO 2, the maximum value (30,4%) was obtained on day nine. The morphometric analyses showed a significant increase in the size of Lulo cells infected at 28°C and J774 cells at 37°C with and without CO 2, respectively.